INTERACTION OF LASER RADIATION WITH MATTER : Processes of interaction of laser radiation with porous transparent materials during their ablation. (26th March 2018) - Osipov, V V; Lisenkov, V V; Platonov, V V; Tikhonov, E V
Abstract: The effect of ytterbium fibre laser radiation with λ = 1.07 μm on the pressed micropowders of transparent oxides and fluorides (CaF2, Y2 O3, Al2 O3, YSZ, etc.) having low absorption coefficients is theoretically studied. Using the numerical modelling, it is established that the radiation scattering in the medium of particles 0.5–4.6 μm in diameter leads to the concentration of radiation in the local regions of the medium, with the intensity level exceeding the intensity of the incident radiation (0.46 MW cm -2 ) by many times. It is shown that with the growth of the refractive index n of the material from 1.38 (MgF2 ) to 2.12 (YSZ) the intensity of radiation in the region of the strongest local maximum increases from 3.8 to 31 MW cm -2 . In our opinion, this factor can be dominant in determining the possibility of achieving the ablation of such a medium by means of the radiation having an intensity of no greater than 1 MW cm -2 . This hypothesis is experimentally checked by the example of preparing a nanopowder of CaF2 (n = 1.43) and 1% Nd : Y2 O3 (n = 1.91) by evaporating the pressed target with the porosity 50% by the continuous-wave radiation of the ytterbium fibre laser with the power 600 W and the intensity 0.4 MW cm -2 . Inside the CaF2 target, the scattered radiation intensity is smaller than the optical breakdown threshold, and the target is not evaporated. Under the same conditions, the target made of higher-melting 1% Nd : Y2 O3 evaporates well, and the efficiency of the nanopowder production amounts to 23 g h -1 .